2014
DOI: 10.1142/s0218202514400065
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on polygonal and polyhedral finite element methods

Abstract: Generalized barycentric coordinates such as Wachspress and mean value coordinates have been used in polygonal and polyhedral finite element methods. Recently, mimetic finite difference schemes were cast within a variational framework, and a consistent and stable finite element method on arbitrary polygonal meshes was devised. The method was coined as the virtual element method (VEM), since it did not require the explicit construction of basis functions. This advance provides a more in-depth understanding of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 131 publications
(170 reference statements)
2
112
0
Order By: Relevance
“…It is seen that the range for the error norms of the VPHE elements are similar to those obtained using Wachspress and mean value coordinate for 2-dimensions as reported in [3] and 3D PFEM as reported in [4] for 3-dimensions. It is also observed that the error norm in heat transfer phenomena is lower.…”
Section: 787×10 -4supporting
confidence: 76%
“…It is seen that the range for the error norms of the VPHE elements are similar to those obtained using Wachspress and mean value coordinate for 2-dimensions as reported in [3] and 3D PFEM as reported in [4] for 3-dimensions. It is also observed that the error norm in heat transfer phenomena is lower.…”
Section: 787×10 -4supporting
confidence: 76%
“…With that choice, a theoretical analysis can be developed using the guidelines in [41] in connection with the same tools and ideas of section 4. Here we prefer to consider the choice (42), which allows for a more direct stability argument. Nevertheless, in the numerical tests of section 5 we will investigate both possibilities.…”
Section: Proof By a Direct Computation It Holds Thatmentioning
confidence: 99%
“…Among the Galerkin schemes, VEM is peculiar in that the discrete spaces consist of functions which are not known pointwise, but about which a limited set of information is available. This limited information is sufficient to construct the stiffness matrix and the right-hand side.The VEM has been developed for many problems; see, for example, [23,1,10,43,46,9,19,17,18,6,42,54,51,37,45]. More specifically, with regard to the Stokes problem, virtual elements have been developed in [3,28,15,25,26,52].…”
mentioning
confidence: 99%
“…These local problems are designed in such a way that the virtual element space includes a subspace of polynomials of some prescribed degree (referred to as the degree of the method) alongside other, typically unknown, virtual functions. In this respect, and like many other conforming approaches to polygonal meshes such as the polygonal finite element method [18,27] or BEM-based FEM [22], the virtual element method falls within the broad class of generalised finite element methods [25]. What sets the virtual element method apart from these other approaches, however, is that the extra non-polynomial virtual functions never need to be determined or evaluated in practice.…”
Section: Introductionmentioning
confidence: 99%